Factor Proportions and Economic Rationality in Soviet Inter- national Trade 1 955-1 968 - Rosefielde, Steven (American Economic Review, 2016)
In 1953, Wassily Leontief made the then startling discovery that the empirical structure of American factor proportions generated in bilateral exchange with the rest of the world contradicted the theoretically anticipated result based on the Heckscher-Ohlin hypothesis. Using the logic of general equilibrium analysis in a two-factor neoclassical model, the Heckscher-Ohlin theorem predicted that America, being relatively abundantly endowed with capital, would produce export goods that intensively embodied capital and import replacement goods intensively embodying the relatively scarce factor labor. By applying the apparatus of input-output analysis, Leontief showed that paradoxically American factor proportions exhibted precisely the opposite relationship to the one anticipated on the basis of the Heckscher-Ohlin theorem. Leontief's finding initiated an avalanche of theoretical and empirical research directed towards unravelling the causal factors responsible for this unexpected and perverse result. Robert Baldwin in a recent article surveyed the evolution of the factor proportions controversy, and since all students of international trade can be expected to be reasonably familiar with the issues at stake, we shall not review them here.